Introducing Social Policy - Alcock, Cliff; Payne, Sarah, 1958-; Sullivan, Michael, 1951- (Harlow : Prentice Hall, 2004)
Social policy as an academic field of study is one of those curious items that we recognise when we see it, but which is notoriously difficult to describe. What exactly is social policy? This text aims to help students to find out.
Previous ed.: 2000.
Includes bibliographical references and index.
Keywords: Society; Great Britain -- Social policy